Estimation of Fluoride and Nitrate in Grund Waters of Arid Regions of Rajasthan Using ION Selective Electronis - Gopal, Ram; Ghosh, P K; Madan, N K (Annals of Arid Zone, 2016)
Standard spectrophotometeric methods are ineffective for the estimation of fluoride and nitrate in polluted / coloured samples of waters. For such waters, the method using ion-selctive Â electrodes is more reliable, simple and rapid. Ground-waters of arid western Rajasthan containing high concentration of chlorides, bicarbonates, sulphates and other dessolved salts were analysed for fluoride and nitrate contents by this method. In high fluoride wters, there existed positive linear relationship between F- and HCO2- and negative relationship between F- and ( Ca2+ Ma2+). Concentration of Mg2+ was generally higher than that of Ca2+ in high fluoride waters.